Η εποχικότητα στους δείκτες ρευστότητας: η ελληνική εμπειρία (1974-1998) - Ξενάκης, Ανδρέας Σ. (SPOUDAI Journal of Economics and Business, 2001)
This paper "Seasonality in Liquidity Indicators - The Greek Experience: 1974-1998" examines the deterministic and stochastic behavior of the seasonal component of four economic time series and their natural logarithms, representing various concepts of Greek liquidity indicators. The four series are the currency in circulation (MO), the money supply in narrow sense (Ml), the money supply in wide sense (M3) and the new liquidity aggregate (M4N). The whole period examined is divided in three subperiods, according to different financial policies, that is the regulated period (1974-1981), the adaptation period (1982-1993) and the financial liberalization period (1994-1998). The examination shows that the seasonal component of the four monetary series contains both deterministic and stochastic features. The deterministic part of the seasonal component exhibits a weakly increasing variability in time for the first three series, while the stochastic part seams to have the same Ι(1,1) integrated pattern for all series and periods. A modified OCSB test for seasonal unit roots is applied, taking into account the moving average, seasonal and non-seasonal, part of the series and using proper critical values, specifically calculated for each case. JEL Classification: C15, C22, E51